The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fbioe.2022.851768
|View full text |Cite
|
Sign up to set email alerts
|

Bioprospecting Kluyveromyces marxianus as a Robust Host for Industrial Biotechnology

Abstract: Kluyveromyces marxianus is an emerging non-conventional food-grade yeast that is generally isolated from diverse habitats, like kefir grain, fermented dairy products, sugar industry sewage, plants, and sisal leaves. A unique set of beneficial traits, such as fastest growth, thermotolerance, and broad substrate spectrum (i.e., hemi-cellulose hydrolysates, xylose, l-arabinose, d-mannose, galactose, maltose, sugar syrup molasses, cellobiose, and dairy industry) makes this yeast a particularly attractive host for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 143 publications
0
11
0
Order By: Relevance
“…Although these expression systems have covered various directions of application, none of them is perfect, and it is important to develop new hosts for recombinant collagen expression, for example, food-grade Kluyveromyces marxianus, lipid-rich Yarrowia lipolytica, probiotic Bacillus subtilis and Lactococcus lactis. [89][90][91][92] K. marxianus is known for its strong secretion capacity, making it an ideal candidate for large-scale fermentation processes. In addition to its robust fermentation characteristics, it is also considered safe for food production.…”
Section: Othersmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these expression systems have covered various directions of application, none of them is perfect, and it is important to develop new hosts for recombinant collagen expression, for example, food-grade Kluyveromyces marxianus, lipid-rich Yarrowia lipolytica, probiotic Bacillus subtilis and Lactococcus lactis. [89][90][91][92] K. marxianus is known for its strong secretion capacity, making it an ideal candidate for large-scale fermentation processes. In addition to its robust fermentation characteristics, it is also considered safe for food production.…”
Section: Othersmentioning
confidence: 99%
“…In addition to its robust fermentation characteristics, it is also considered safe for food production. 89 Y. lipolytica is a yeast widely used in the food industry in recent years and performs better in some extreme and complex environments due to its better acid, alkaline and high-temperature tolerance. 90 The applications of B. subtilis and B. brevis are similar, but the biotechnologies of B. subtilis are relatively more mature and widely used.…”
Section: Selection and Future Directions Of Expression Systemsmentioning
confidence: 99%
“…Upgrading Non-conventional Yeasts into Valuable Biofactories DOI: http://dx.doi.org/10.5772/intechopen.109903 alternative to baker's yeast; bioremediation of textile dyes, cheese whey and copper; biomass for animal feeding; probiotics and high-temperature bioethanol production [67,69,72,73,75]. For instance, Nonklang et al found remarkable differences in high-temperature ethanol production between S. cerevisiae and K. marxianus as K. marxianus DMKU3-1042 was the fastest to convert glucose to ethanol at 45°C whereas none of the S. cerevisiae strains were able to grow at this temperature [67].…”
Section: Kluyveromyces Marxianusmentioning
confidence: 99%
“…Some advantages of working with K. lactis yeasts are the capacity of producing heterologous proteins in simple growth medium, complete knowledge of their genome and more importantly, they can be easily genetically manipulated [75]. Due to its similarity in biosynthetic capacities to S. cerevisiae, K. lactis toolkits for heterologous gene expression are mostly the same.…”
Section: Kluyveromyces Lactismentioning
confidence: 99%
“…Promising unconventional chassis cells include the yeasts Yarrowia lipolytica, Kluyveromyces, and Pichia pastoris, and the bacterium Corynebacterium glutamicum. Yarrowia lipolytica is primarily used for the production of proteins, oils, terpenes, organic acids, and sugar alcohols due to the su cient supply of acetyl-CoA and NADPH and the low glycosylation level of protein [8][9][10]; Kluyveromyces marxianus has been successfully used in the production of biofuel ethanol and aromatic compounds due to its bene cial traits including wide substrate utilization, rapid growth and high temperature tolerance [11][12][13][14]. Pichia pastoris is widely used in the production of heterologous proteins due to high protein secretion capacity and low glycosylation level, and is also used as a one-carbon carbon source utilization chassis due to the natural methylotrophic characteristics [15].…”
Section: Introductionmentioning
confidence: 99%